Crafting math minds: A bibliometric odyssey into innovative didactical designs for learning (2006-2023) - Dasari, Dadan; Muhammad, Ilham; Juandi, Dadang (Jurnal Elemen, 2024)
The importance of Didactical Design in mathematics education must be addressed. Didactical Design is essential in mathematics education because it can optimize learning. Efforts to design learning experiences that combine didactic and design principles can lead students to acquire knowledge correctly and epistemically. This research aims to capture the landscape of previous research relevant to Didactical Design in Mathematics Education. This study constitutes a literature review research, wherein 56 publications were gathered from the Scopus database. These publications were subsequently subjected to bibliometric analysis with the assistance of the VOSviewer application. The analysis results show a rapid increase in publications since 2019, primarily focusing on didactic design, barriers to student learning, mathematics education, and retrospective analysis. The study also identified the emergence of new themes in Didactical Design research, such as the study of specific mathematical competencies and the integration of technology in design, e-learning, augmented reality, and STEM. Several implications are presented as helpful information for scientists and stakeholders.